Transgenic oat for improved BYDV resistance - Nuutila, Anna Maria; Lehto, Kirsi; Oksman-Caldentey, Kirsi-Marja (MTT, 2004)
Among the cereal crops cultivated in Finland oat (Avena sativa L.) ranks second, after barley. Finland is one of the major oat producers in the world and a considerable part of the harvest is exported. The Finnish oat cultivars are generally well adapted to the humid and cool growth conditions in Finland. In order to improve the Finnish oat cultivars better to meet the requirements of the food industry, modern biotechnical methods are being used. Our first aim was to develop oat varieties with resistance to BYDV (Barley Yellow Dwarf Virus) through gene transfer. Six Finnish oat cultivars were used. The genotypes Kolbu, Rhiannon, GP-1 and Avena sterilis were used as controls. Cell cultures were started from mature embryos of all of these cultivars. From two Finnish cultivars leaf bases were also used. Embryogenic tissue cultures or oat leaf bases were used as targets for gene transfer, which was accomplished using particle bombardment. The transformants from the gene transfer experiments with the BYDV resistance gene were regenerated and rooted on selection media and transferred in soil in the greenhouse. Transgenic plants carrying the BYDV resistance gene were obtained only from those embryogenic cell cultures, which were started from mature embryos of oat. The progeny of these transgenic plants was germinated and screened for the inheritance of the transgene. The germination frequency of the seeds has been good, for example ranging from 92 to 100 % in T1 and in T2, respectively. The progeny carrying the BYDV resistance gene was submitted to viral resistance testing.
Keywords: Ka; oat; transgenic; BYDV resistance; Avena